ADAM12 is a circulating marker for stromal activation in pancreatic cancer and predicts response to chemotherapy. (November 2018) - Veenstra, V.; Damhofer, H.; Waasdorp, C.; Rijssen, L.; Vijver, M.; Dijk, F.; Wilmink, H.; Besselink, M.; Busch, O.; Chang, D.; Bailey, P.; Biankin, A.; et al.
Abstract Pancreatic ductal adenocarcinoma (PDAC) is characterized by abundant stroma that harbors tumor-promoting properties. No good biomarkers exist to monitor the effect of stromal targeting therapies or to predict response. We set out to identify such non-invasive markers for PDAC stroma and predict response to therapy. Gene expression datasets, co-culture experiments, xenografts, and patient samples were analyzed. Serum samples were measured from a cohort of 58 resected patients, and 87 metastatic or locally advanced PDAC patients. Baseline and follow-up levels were assessed in 372 additional metastatic PDAC patients who received nab-paclitaxel with gemcitabine (n  =  184) or gemcitabine monotherapy (n  =  188) in the phase III MPACT trial. Increased levels of ADAM12 were found in PDAC patients compared to healthy controls (p  < 0.0001, n  =  157 andn  =  38). High levels of ADAM12 significantly associated with poor outcome in resected PDAC (HR 2.07, p  =  0.04). In the MPACT trial survival was significantly longer for patients who received nab-paclitaxel and had undetectable ADAM12 levels before treatment (OS 12.3 m vs 7.9 mp  = 0.0046). Consistently undetectable or decreased ADAM12 levels during treatment significantly associated with longer survival as well (OS 14.4 m and 11.2 m, respectively vs 8.3, p  =  0.0054). We conclude that ADAM12 is a blood-borne proxy for stromal activation, the levels of which have prognostic significance and correlate with treatment benefit.